The implications of mandible morphology and dental structure on the feeding ecology and predatory behaviour in Hyaenidae (hyenas) using geometric morphometric analyses - Nadioo, Riyanta (University of the Witwatersrand, Johannesburg, 2024)
Hyenas are often overlooked as being successful predators due to their scavenging behaviour. However, their morphological adaptations allow them to succeed in bone-cracking behaviour, an act that most carnivores are unable to achieve. Craniodental morphology influences carnivore performance, therefore understanding the functional morphology of carnivore mandibles would allow for the justification of Hyaenidae behaviour. This study investigates the morphological differences between the Hyaenidae mandible and large carnivore mandibles in Africa, as well as the differences in mandible morphology within the Hyaenidae family. This study uses a two-dimensional landmark-based geometric morphometric methodology to analyse morphological features on the carnivore mandibles and dentition to determine the morphological clusters linking the carnivore species, determine how the mandible morphology accommodates biomechanical needs, and to determine the implications that mandible morphology and dentition has on feeding ecology. The results of this study indicated that the sizes (PC1) of the carnivore mandibles were clustered according to their respective families (i.e. Hyaenidae, Canidae, and Felidae), however the shape (PC2) of the mandibles differed according to diet. The mandible morphology of the hypercarnivorous Hyaenidae displayed evident adaptations to osteophagy behaviour, including a thickened corpus, a large masseteric fossa, an anteriorly-displaced coronoid, and robust and blunt-like canines. The Proteles cristata, however, displayed mandibular adaptations to a hypocarnivorous diet. Ultimately, it was found that an increased resistance to bending forces and an increased area for muscle attachment on the mandible, directly relates to an increase in the Hyaenidae bite force, improving their feeding and hunting success.
A Dissertation Submitted in fulfillment of the requirements for the degree Master of Science in Animal, Plant and Environmental Sciences in the Faculty of Science, University of the Witwatersrand, Johannesburg, South Africa 2024
Keywords: Bite force; feeding ecology; geometric morphometrics; mandible morphology; osteophagy; SDG-15: Life on land